PENTINGNYA PEMBELAJARAN MOBILE, KEARIFAN LOKAL, DAN KEPARIWISATAAN - Firman Septiawan; Nur Azizah; Paras Purnama Gita; Yusran Khery (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2019)
This study aims to evaluate the application of local wisdom-oriented mobile learning and tourism in West Nusa Tenggara. This type of research is a descriptive study carried out by survey method. The research subjects consisted of 32 students of biology education in semester III and semester V of Mandalika University of Education in the academic year 2019-2020, taken by simple random technique. Data on the application of learning based on local wisdom and tourism was obtained using an observation questionnaire on the application of learning based on local wisdom and tourism in West Nusa Tenggara. The results showed that, the lowest score of aspects of tourism-based learning and local wisdom lies in the lecture aspect starting with the tourism context of West Nusa Tenggara at 53.91 with sufficient categories. While the highest score of lectures was delivered practically related to local products typical of the people of West Nusa Tenggara with a high category of 63.28. Two aspects of learning based on local wisdom and tourism have enough categories namely the lecture aspect starts with the West Nusa Tenggara tourism context to develop knowledge about tourism. While the rest are in the good category.